THE INFLUENCE OF ORGANIZATIONAL COMMUNICATION ON EMPLOYEE ENGAGEMENT - Riani Prihatini Ishak; Made Ayu Anggreni; Dhiraj Kelly Sawlani (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to examine the influence of organizational communication on employe engagement thru a literature review approach. Employe engagement has become one of the important factors in improving organizational performance because it is related to the emotional, cognitive, and behavioral involvement of employes with their work and the organization. Organizational communication serves as the main tool in building trust, transparency, and effective working relationships between leaders and employes. The research method used is a literature review by analyzing various reputable national and international journal articles relevant to the research topic. Data analysis was conducted using a thematic analysis approach and literature synthesis to identify patterns of relationships between organizational communication and employe engagement. The study results show that organizational communication has a significant impact on employe engagement thru several key mechanisms, namely increased job satisfaction, communicative leadership, and the creation of a positive communication environment. Open, transparent, and two-way communication has proven to enhance employes' sense of appreciation, trust, and work motivation. Additionally, the quality of internal communication, which includes clarity of task information, feedback provision, and supportive communication, becomes an important determinant in building employe engagement. Theoretically, this research reinforces the role of organizational communication from the perspective of organizational behavior and human resource management. Practically, the research findings provide implications for organizations to develop effective internal communication strategies to sustainably enhance employe engagement.